Unveiling microscale aerosol formation pathways in combustion systems: in situ evidence from cigarette burning cones - Jiaying Li; Huapeng Cui; Meijuan Fan; Li Chen; Yaqiong Qin; Ruihong Liu; Mantang Chen; Yu Liu; Jizhao Guo; Shaofeng Liu; Xiaobing Zhang; Fuwei Xie; et al. (Biomass and Bioenergy, 2026)

Noncovalent interaction between β-conglycinin and rutin: Structural characterization, binding mechanism and emulsifying stability - Fuwei Sun; Haotian Liu; Chaojiang Dong; Yang Li; Zengwang Guo; Lianzhou Jiang; Zhongjiang Wang; Fang Kou (Food Hydrocolloids, 2026)

Microenvironment modulation of single-atom Rh sites via fluorinated phosphine polymer skeleton engineering toward boosted hydroformylation performance - Li Huang; Miaojiang Wu; Peng Sun; Mengnan Nie; Yulong Lai; Guang Gao; Zhiwei Huang; Fuwei Li (Chemical Engineering Journal, 2026)

An all-in-one nanocomposite hydrogel-based wearable multimodal sensor for strain sensing and sweat ascorbic acid monitoring - Fuwei Wang; Yaxin Chen; Jingjuan Wang; Yajuan Li; Xudong Yu (Chemical Engineering Journal, 2026)

Leonurine-ligated nanozymes: A feasible therapeutic avenue for anti-inflammatory intervention in Parkinson's disease - Yingying Wang; Qing Liu; Chang Liu; Xiaoxi Chen; Ruijun Li; Wanying Chen; Fuwei Yang (Chemical Engineering Journal, 2026)

Cavitation jet-assisted construction of the soybean protein-based high internal phase emulsions: interfacial behaviors, formation mechanisms in 3D printing and improved bioaccessibility of γ-oryzanol - Fuwei Sun; Fang Kou; Yiying Jin; Meiyun Li; Caihua Liu; Meng Yuan; Lianzhou Jiang; Zengwang Guo; Zhongjiang Wang; Haotian Liu (Food Hydrocolloids, 2026)

A novel 3D-printed flexible electrode with rGO/MWCNTs ink for capsaicin detection in chilli peppers - Jiachen Zhao; Huilin Hu; Chao Wang; Yingting Li; Xueyu Jiang; Ming Zhang; Fangkai Han; Ning Yang; Xiaodan Liu; Jiahua Wang; Yingli Wang; Shuo Duan; et al. (Food Chemistry, 2026)

Effect of dextran molecular weight on Maillard glycation of soy protein isolate: Structural modifications and flavor-binding behavior - Xuejie Li; Yaqiong Qin; Bing Wang; Cong Wang; Mantang Chen; Ruihong Liu; Kejian Liu; Cong Nie; Fuwei Xie; Xiaoyu Wang; Wentao Zhang; Jian Li (Food Hydrocolloids, 2026)

A fluorescence-colorimetric dual-mode strategy for smartphone sensing of tetracycline antibiotics - Junjie Qi; Jingkun Li; Yuqi Wan; Guoyong Jiang; Yukihiro Ozaki; Fuwei Pi (Food Control, 2026)

Characterization of volatile flavour compounds and characteristic flavour precursors in poultry eggs based on multi-omics and machine learning - Hongqiang Li; Xiangmin Zhao; Xiaoming Li; Jing Liang; Shizhen Qin; Jinlu Li; Aiwen Zhang; Linna Xu; Defu Tang; Fuwei Li (Food Chemistry, 2025)

Plateau zokor mounds decrease soil respiration by shifting microenvironment - Fanglong Su; Fuwei Wang; Donghui Li; Yueqing Xu; Zhongling Yang; Yue Du; Renhui Miao (CATENA, 2025)

Cationic covalent organic framework for synergistic adsorption and reduction of Au(III) and Cr(VI) ions - Jingkun Li; Guoyong Jiang; Yuqi Wan; Junjie Qi; Fuwei Pi (Chemical Engineering Journal, 2025)

Canopy nitrogen and water addition affect fine-root survival strategies and carbon allocation in a warm-temperate forest in China - Wen Li; Yanzhu Su; Yiwen Qin; Fuwei Li; Tenglong Zhou; Yaqi He; Jianing Mao; Mengke Li; Chang Liu; Yifei Shi; Dandan Zhu; Chunyu Shen; et al. (Forest Ecology and Management, 2025)

A novel approach for identifying sweet spots in tight reservoir fracturing engineering based on physical-data dual drive - Huohai Yang; Fuwei Li; Wei Wang; Yu Fu; Qinxi Tang; Jie Yang; Binghong Xie (Journal of Applied Geophysics, 2025)

On-line adapted islands SERS Chip for quantitatively sensing H2S molecules in food spoilage - Xiaohui Wang; Yuqi Wan; Jingkun Li; Yukihiro Ozaki; Jiahua Wang; Fuwei Pi (Food Chemistry, 2025)

Insight into the principles and advanced construction strategies of nanoprobe based multi-targets sensing in food safety - Xiaohui Wang; Guoyong Jiang; Yuqi Wan; Jingkun Li; Sa-adu Abiola Dauda; Harriet Sonia Nalumansi; Jiahua Wang; Fuwei Pi (Food Chemistry, 2025)

A sheltering ratio fluorescence composite based on BR-CDs for selectivity detection of GSH - Yuqi Wan; Shuqi Li; Jiahua Wang; Fuwei Pi (Food Chemistry, 2025)

Spotlight on the long-term effects of micro/nanoplastics exposure on Spirulina platensis: Algal cells, extracellular polymeric substances, and phycocyanin - Zhiheng Yue; Jiangjin Qian; Wenjing Li; Xiaodan Liu; Huang Dai; Xin Liu; Fuwei Pi; Jiahua Wang (Food Chemistry, 2025)

Upcycling CO2 and bio-derived furan into degradable plastic monomer via coupling of photocatalysis and thermocatalysis - Qi Liu; Chengyang Li; Tingting Wang; Peng Sun; Jia Wang; Yongjie Xi; Guang Gao; Mengnan Nie; Li Huang; Guofeng Wang; Zelun Zhao; Zhiwei Huang; et al. (Chemical Engineering Journal, 2024)

Responses of coastal phytoplankton communities to seasonal herbicide inputs: Tolerance or degeneration? - Yunsheng Wang; Ying Chen; Fuwei Zhang; Lingxiao Li; Shaoguo Ru; Liqiang Yang (Journal of Hazardous Materials, 2024)

Additive patterns in near-infrared diffuse reflectance spectra: Implications for product formulation and analysis - Le Zhao; Youyan Liang; Nuohan Zhang; Yanbin Chang; Meijuan Fan; Cong Wang; Beibei Li; Hongbo Wang; Yu Liu; Hongxiao Yu; Song Yang; Fuwei Xie; et al. (Food Control, 2024)

Optimizing acid microemulsions for cleaner gas production: A study on enhanced adsorption characteristics and implications in retardation - Qing Wang; Fujian Zhou; Hang Su; Hongtao Fei; Yuan Li; Fuwei Yu; Rencheng Dong; Erdong Yao; Zhangxin Chen (Science of The Total Environment, 2024)

Tunable magnetism and band structure in kagome materials RETi3Bi4 family with weak interlayer interactions - Jingwen Guo; Liqin Zhou; Jianyang Ding; Gexing Qu; Zhengtai Liu; Yu Du; Heng Zhang; Jiajun Li; Yiying Zhang; Fuwei Zhou; Wuyi Qi; Minghui Cui; et al. (Science Bulletin, 2024)

Spectroscopy combined with spatiotemporal multiscale strategy to study the adsorption mechanism of soybean protein isolate with meat flavor compounds (furan): Differences in position and quantity of the methyl - Yang Li; Jing Xu; Fuwei Sun; Yanan Guo; Daoying Wang; Tianfu Cheng; Minwei Xu; Zhongjiang Wang; Zengwang Guo (Food Chemistry, 2024)

Characterization of HIPEs stabilized by soy protein isolate with excellent rheological properties for 3D printing: Bridging the correlation among structure, function and application - Meng Yuan; Bailiang Li; Fuwei Sun; Tianfu Cheng; Jun Liu; Daoying Wang; Zengwang Guo; Zhongjiang Wang (Food Hydrocolloids, 2024)

Luminescent carbon dots-rooted polysaccharide crosslinked hydrogel adsorbent for sensitive determination and efficient removal of Cu2+ - Jingkun Li; Liying Wang; Guoyong Jiang; Yuqi Wan; Jiahua Wang; Yan Li; Fuwei Pi (Food Chemistry, 2024)

Changes in microbial composition explain the contrasting responses of glucose and lignin decomposition to soil acidification in an alpine grassland - Fuwei Wang; Yue Gao; Xin Li; Mengdi Luan; Xiaoyi Wang; Yanwen Zhao; Xianhui Zhou; Guozhen Du; Peng Wang; Chenglong Ye; Hui Guo (Science of The Total Environment, 2024)

Investigation of the in vitro toxic effects induced by real-time aerosol of electronic cigarette solvents using microfluidic chips - Zezhi Li; Xiang Li; Boyang Feng; Junwei Zhao; Kejian Liu; Fuwei Xie; Jianping Xie (Food and Chemical Toxicology, 2024)

Different responses of marine microalgae Phaeodactylum tricornutum upon exposures to WAF and CEWAF of crude oil: A case study coupled with stable isotopic signatures - Yadi Lou; Ying Wang; Shiyue Li; Fuwei Yu; Xing Liu; Yi Cong; Zhaochuan Li; Fei Jin; Mingxing Zhang; Ziwei Yao; Juying Wang (Journal of Hazardous Materials, 2024)

Oral delivery of berberine by liver-targeted zwitterionic nanoparticles to overcome multi-intestinal barriers and extend insulin treatment duration - Yuhong Ma; Caihua Li; Fuwei Han; Yunzhu Liu; Umm E Hani; Yinan Zhong; Dechun Huang; Wei Chen; Hongliang Qian (Chemical Engineering Journal, 2024)

Analysis of the response to cigarette smoke exposure in cell coculture and monoculture based on bionic-lung microfluidic chips - Zezhi Li; Boyang Feng; Xiang Li; Junwei Zhao; Kejian Liu; Fuwei Xie; Jianping Xie (Analytica Chimica Acta, 2024)

Non-destructive detection and grading of chilling injury-induced lignification of kiwifruit using X-ray computer tomography and machine learning - Jiahua Wang; Yuqing Lin; Qiaocong Li; Zelin Lu; Jiangjin Qian; Huang Dai; Fuwei Pi; Xiaodan Liu; Yong He (Computers and Electronics in Agriculture, 2024)

A fluorescence and SERS dual-mode sensing on tetracycline antibiotics based on Ag@NH2-MIL-101(Al) nanoprobe - Junjie Qi; Jingkun Li; Yuqi Wan; Yu Li; Fuwei Pi (Food Chemistry, 2024)

Enhanced stability of hierarchical zeolite-metal bifunctional catalysts for conversion of levulinic acid to valeric biofuels - Chengyang Li; Jia Wang; Guang Gao; Zelun Zhao; Peng Sun; Fuwei Li (Chemical Engineering Journal, 2024)

Self-assembly kieselguhr-based ZSM-5 for catalytic pyrolysis of mask waste to produce high value-added aromatics - Yufei Gu; Hucheng Ge; Yuke Liu; Qi Wei; Tianhua Gao; Hengshuo Gu; Hongbing Fu; Fuwei Li; Hongfei Lin; Lei Miao; Zhixia Li (Fuel, 2024)

Progress on aptamer-based SERS sensors for food safety and quality assessment: methodology, current applications and future trends - Guoyong Jiang; Yu Li; Jinghan Liu; Ling Liu; Fuwei Pi (Critical Reviews in Food Science and Nutrition, 2024)

A novel approach for evaluating the transport capacity of sandstone carriers and determining effective hydrocarbon migration channels: Application to the Pinghu Slope Belt of the Xihu Depression, East China Sea Basin - Fuwei Wang; Dongxia Chen; Meijun Li; Zhangxin Chen; Qiaochu Wang; Khawaja Hasnain Iltaf; Sha Li; Wenzhi Lei; Mengya Jiang; Yuqi Wang; Lanxi Rong (Journal of Asian Earth Sciences, 2024)

Enhanced photocatalytic and antimicrobial activities of carbon-dots nanozymes modulated with P-doping - Guoyong Jiang; Jiawen Fan; Yuqi Wan; Jingkun Li; Fuwei Pi (Chemical Engineering Journal, 2024)

Intramolecular charge transfer-induced fluorochromic covalent organic frameworks for high speed on-line monitoring of volatile amines - Jingkun Li; Yuqi Wan; Guoyong Jiang; Yukihiro Ozaki; Fuwei Pi (Chemical Engineering Journal, 2024)

Combined resource utilization of ash from biomass power generation and wheat straw biochar for soil remediation - Xingxiu Huang; Genxing Pan; Lianqing Li; Xuhui Zhang; Hailong Wang; Nanthi Bolan; Bhupinder Pal Singh; Chongjian Ma; Fuwei Liang; Yanjie Chen; Huashou Li (Applied Soil Ecology, 2024)

Combining a lung microfluidic chip exposure model with transcriptomic analysis to evaluate the inflammation in BEAS-2B cells exposed to cigarette smoke - Zezhi Li; Xiang Li; Boyang Feng; Jingxian Xue; Junwei Zhao; Qingqing Zhu; Kejian Liu; Fuwei Xie; Jianping Xie (Analytica Chimica Acta, 2024)

An inter-provincial carbon quota study in China based on the contribution of clean energy to carbon reduction - Wei Shi; Wei Li; Fuwei Qiao; Weijuan Wang; Yi An; Guowei Zhang (Energy Policy, 2023)

Routine analysis of pesticides in foodstuffs: Emerging ambient ionization mass spectrometry as an alternative strategy to be on your radar - Jingkun Li; Jinghan Liu; Yuqi Wan; Jiahua Wang; Fuwei Pi (Critical Reviews in Food Science and Nutrition, 2023)

Low air pressure self-sustaining combustion performances of 3D direct writing Al/CuO film - Yuxuan Zhou; Yueting Wang; Zehua Zhang; Fuwei Li; Jian Cheng; Yinghua Ye; Jianbing Xu; Ruiqi Shen (Chemical Engineering Journal, 2023)

Risk SNP in a transcript of RP11-638I2.4 increases lncRNA–YY1 interaction and pancreatic cancer susceptibility - Ming Zhang; Yanmin Li; Fuwei Zhang; Hui Geng; Yimin Cai; Zequn Lu; Bin Li; Caibo Ning; Wenzhuo Wang; Haijie Li; Jianbo Tian; Ying Zhu; et al. (Archives of Toxicology, 2023)

A Machine-Learning Approach Based on Attention Mechanism for Significant Wave Height Forecasting - Jiao Shi; Tianyun Su; Xinfang Li; Fuwei Wang; Jingjing Cui; Zhendong Liu; Jie Wang (Journal of Marine Science and Engineering, 2023)
Significant wave height (SWH) is a key parameter for monitoring the state of waves. Accurate and long-term SWH forecasting is significant to maritime shipping and coastal engineering. This study proposes a transformer model based on an attention mechanism to achieve the forecasting of SWHs. The transformer model can capture the contextual information and dependencies between sequences and achieves continuous time series forecasting. Wave scale classification is carried out according to the forecasting results, and the results are compared with gated recurrent unit (GRU) and long short-term memory (LSTM) machine-learning models and the key laboratory of MArine Science and NUmerical Modeling (MASNUM) numerical wave model. The results show that the machine-learning models outperform the MASNUM within 72 h, with the transformer being the best model. For continuous 12 h, 24 h, 36 h, 48 h, 72 h, and 96 h forecasting, the average mean absolute errors (MAEs) of the test sets were, respectively, 0.139 m, 0.186 m, 0.223 m, 0.254 m, 0.302 m, and 0.329 m, and the wave scale classification accuracies were, respectively, 91.1%, 99.4%, 86%, 83.3%, 78.9%, and 77.5%. The experimental results validate that the transformer model can achieve continuous and accurate SWH forecasting, as well as accurate wave scale classification and early warning of waves, providing technical support for wave monitoring.

Bisphenol A decreases the developmental toxicity and histopathological alterations caused by polystyrene nanoplastics in developing marine medaka Oryzias melastigma - Fuwei Yu; Fei Jin; Yi Cong; Yadi Lou; Zhaochuan Li; Ruijing Li; Baojun Ding; Ying Wang; Jingwen Chen; Juying Wang (Chemosphere, 2023)

Insight into nanomaterials mediated dual-modal assay for food safety: Design principles and applications - Gengli Huang; Xueli Luo; Guoyong Jiang; Yu Li; Sa-adu Abiola Dauda; Jiayi Li; Fuwei Pi (Trends in Food Science & Technology, 2023)

Enhancing the combustion and propulsion performance of Al/CuO via introducing AlH3 as fuel substitute - Keer Ouyang; Jian Cheng; Zehua Zhang; Fuwei Li; Yinghua Ye; Ruiqi Shen (Fuel, 2023)

Microwave controlled ignition and combustion characteristics of ADN-based ionic liquid propellant with fast response and environmental friendliness - Jian Cheng; Jinle Cao; Fuwei Li; Zehua Zhang; Jianbing Xu; Keer Ouyang; Carole Rossi; Yinghua Ye; Ruiqi Shen (Chemical Engineering Journal, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

Fabrication of soy protein isolate - High methoxyl pectin composite emulsions for improving the stability and bioavailability of carotenoids - Jiayi Li; Gengli Huang; He Qian; Fuwei Pi (Food Bioscience, 2023)

Evaluation of cigarette smoke-induced oxidative stress and inflammation in BEAS-2B cells based on a lung microfluidic chip - Jingxian Xue; Zezhi Li; Xiang Li; Chenfeng Hua; Pingping Shang; Junwei Zhao; Kejian Liu; Fuwei Xie (Food and Chemical Toxicology, 2023)

Earth-abundant Co nanoparticles encapsulated in N-doped hollow carbon sphere for highly selective hydrodeoxygenation of biomass-derived vanillin - Jun Wu; Ming Jin; Yong Li; Junfeng Zhao; Tingting Wang; Yuhang Xie; Liqian Liu; Chengbing Wang; Fuwei Li (Chemical Engineering Journal, 2023)

Effects of torularhodin against acetaminophen induced liver injury base on antioxidation, anti-inflammation and anti-apoptosis - Jiayi Li; He Qian; Fuwei Pi (Food Bioscience, 2023)

Electrodeposition cobalt sulfide nanosheet on laser-induced graphene as capacitive deionization electrodes for uranium adsorption - Ruya Cao; Jianfeng Zhang; De Wang; Fuwei Sun; Nian Li; Jiaxing Li (Chemical Engineering Journal, 2023)

Catalytic co-cracking of biomass and waste plastics with sawdust mediated ZSM-5 synthesized via activating gel process - Fuwei Li; Xiaofeng Wang; Hengshuo Gu; Hongbing Fu; Asad Ali; Hongfei Lin; Zhixia Li (Fuel, 2023)

Coaxial electrospinning fabrication of core-shell energetic fibers and in-situ integration with SCB exhibiting superior non-contact ignition - Zehua Zhang; Jian Cheng; Yueting Wang; Fuwei Li; Yun Shen; Cheng-ai Wang; Jianbing Xu; Ruiqi Shen; Yinghua Ye (Chemical Engineering Journal, 2023)

Doping of Al/CuO with microwave absorbing Ti3C2 MXene for improved ignition and combustion performance - Jian Cheng; Zehua Zhang; Yueting Wang; Fuwei Li; Jinle Cao; Michael Gozin; Yinghua Ye; Ruiqi Shen (Chemical Engineering Journal, 2023)

Sensitive Groups of Bacteria Dictate Microbial Functional Responses to Short-term Warming and N Input in a Semiarid Grassland - Fuwei Wang; Zhen Li; Fanglong Su; Hui Guo; Peng Wang; Jiuxin Guo; Weixing Zhu; Yi Wang; Shuijin Hu (Ecosystems, 2022)

Petrogenesis of Early-Middle Jurassic gabbros in southern Tibet with implications for crustal growth in the southern Lhasa subterrane - Liang Li; Hui Xie; Xinghai Lang; Xuhui Wang; Qing He; Yulin Deng; Fuwei Xie (International Geology Review, 2022)

Laboratory investigation of the shear failure process and strength characteristics of a rock mass containing discontinuous joints under water pressure influence - Xuxu Yang; Lichao Li; Panpan Sun; Shicheng Wang; Fuwei Li (Bulletin of Engineering Geology and the Environment, 2022)

Sensitive Techniques for POCT Sensing on the Residues of Pesticides and Veterinary Drugs in Food - Lin Liu; Yueying Gao; Jinghan Liu; Ying Li; Ziye Yin; Yuanyuan Zhang; Fuwei Pi; Xiulan Sun (Bulletin of Environmental Contamination and Toxicology, 2021)

Current Progress on Antibiotic Sensing Based on Ratiometric Fluorescent Sensors - Jinghan Liu; Ying Li; Lin Liu; Yueying Gao; Yuanyuan Zhang; Ziye Yin; Fuwei Pi; Xiulan Sun (Bulletin of Environmental Contamination and Toxicology, 2021)

Interactive global change factors mitigate soil aggregation and carbon change in a semi‐arid grassland - Tongshuo Bai; Peng Wang; Steven J. Hall; Fuwei Wang; Chenglong Ye; Zhen Li; Shijie Li; Luyao Zhou; Yunpeng Qiu; Jiuxin Guo; Hui Guo; Yi Wang; et al. (Global Change Biology, 2020)
The ongoing global change is multi‐faceted, but the interactive effects of multiple drivers on the persistence of soil carbon (C) are poorly understood. We examined the effects of warming, reactive nitrogen (N) inputs (12 g N m −2 year −1 ) and altered precipitation (+ or − 30% ambient) on soil aggregates and mineral‐associated C in a 4 year manipulation experiment with a semi‐arid grassland on China's Loess Plateau. Our results showed that in the absence of N inputs, precipitation additions significantly enhanced soil aggregation and promoted the coupling between aggregation and both soil fungal biomass and exchangeable Mg 2+ . However, N inputs negated the promotional effects of increased precipitation, mainly through suppressing fungal growth and altering soil pH and clay‐Mg 2+ ‐OC bridging. Warming increased C content in the mineral‐associated fraction, likely by increasing inputs of root‐derived C, and reducing turnover of existing mineral‐associated C due to suppression of fungal growth and soil respiration. Together, our results provide new insights into the potential mechanisms through which multiple global change factors control soil C persistence in arid and semi‐arid grasslands. These findings suggest that the interactive effects among global change factors should be incorporated to predict the soil C dynamics under future global change scenarios.

Genome-wide association study of body weight in Wenshang Barred chicken based on the SLAF-seq technology - Fuwei Li; Haixia Han; Qiuxia Lei; Jinbo Gao; Jie Liu; Wei Liu; Yan Zhou; Huimin Li; Dingguo Cao (Journal of Applied Genetics, 2018)

A comparative study on the landslide susceptibility mapping using logistic regression and statistical index models - Zhiyong Wu; Yanli Wu; Yitian Yang; Fuwei Chen; Na Zhang; Yutian Ke; Wenping Li (Arabian Journal of Geosciences, 2017)

Porcine bocavirus NP1 protein suppresses type I IFN production by interfering with IRF3 DNA-binding activity - Ruoxi Zhang; Liurong Fang; Wei Wu; Fuwei Zhao; Tao Song; Lilan Xie; Yi Li; Huanchun Chen; Shaobo Xiao (Virus Genes, 2016)

Cytotoxicity and mutagenicity of sidestream cigarette smoke particulate matter of different particle sizes - Xiang Li; Bencheng Lin; Huashan Zhang; Fuwei Xie; Na Ta; Lei Tian; Huimin Liu; Zhuge Xi (Environmental Science and Pollution Research, 2016)

Variation and genetic stability analyses of transgenic TaLEA poplar clones from four different sites in China - Mengran Liu; Shaopeng Yin; Dongjing Si; Longting Shao; Ying Li; Mi Zheng; Fuwei Wang; Shuchun Li; Guifeng Liu; Xiyang Zhao (Euphytica, 2015)

Responses of energy balance, physiology, and production for transition dairy cows fed with a low-energy prepartum diet during hot season - Huawei Su; Yachun Wang; Qian Zhang; Fuwei Wang; Zhijun Cao; Muhammad Aziz Ur Rahman; Binghai Cao; Shengli Li (Tropical Animal Health and Production, 2013)